Melampaui Promosi: Tata Kelola, Kapasitas Institusional, dan Strategi Pemasaran dalam Pengembangan Destinasi Pariwisata Pinggiran - Moriolkosu, Jhon Rien; Rumra, Fatmawati; Bandjar, Antasari (Universitas Pattimura, 2025)
This article aims to evaluate governance, institutional capacity, and marketing strategies in the development of peripheral tourism destinations, using Matakus Beach in the Tanimbar Islands Regency as a case study. The study employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and document analysis of promotional practices implemented by the local Tourism Office. The findings reveal that the promotion strategies applied align with the principles of the promotion mix, utilizing advertising, sales promotion, direct marketing, and public relations. However, personal selling methods have not been optimally implemented. The main challenges identified include budget constraints and limited human resources, which have affected the effectiveness of the promotional strategies. These findings contribute to a deeper understanding of the importance of strengthening institutional capacity in peripheral regions to support sustainable tourism promotion. The novelty of this study lies in its integration of governance and institutional capacity analysis into the evaluation of destination marketing strategies in peripheral areas, which have traditionally focused primarily on promotional aspects. Recommendations are proposed to ensure that the development of peripheral tourism destinations prioritizes not only intensified promotion efforts but also institutional restructuring and resource strengthening as foundations for tourism sustainability. This article is expected to contribute to the advancement of theory and practice in the social sciences and humanities, particularly in the fields of governance and regional tourism marketing studies.